Literature Review Sensory Marketing Analysis: Theoretical Foundations, Practical Applications, and Their Impact on Consumer Behavior - Richadinata, Kadek Riyan Putra; Wardana, I Made; Ekawati, Ni Wayan; Aksari, Ni Made Asti (Journal of Economics and Public Health, 2024)
Sensory marketing has emerged as an important strategy for businesses aiming to create lasting impressions and emotional connections with consumers. This study explores the theoretical foundations, practical applications, and impact of sensory marketing on consumer behavior. Sensory stimuli—such as visual, auditory, olfactory, gustatory, and tactile elements—play a critical role in shaping consumer perceptions and behaviors. The study suggests that sensory marketing not only influences immediate purchase decisions but also fosters long-term brand loyalty by creating memorable experiences. This study systematically reviews the current literature to evaluate the effectiveness of sensory marketing across multiple contexts, including physical retail environments, e-commerce, and the luxury goods market. data search with the keywords typed to search for articles are: "sensory marketing impact on consumer behavior", "sensory marketing impact on purchase intention", "sensory marketing impact on digital purchase decision", "Sensory marketing impact on purchase satisfaction", " sensory marketing impact on Product Perception”, “sensory marketing impact on price perception and “sensory marketing impact on with result 13 article that meet the inclusion and exclusion criteria” from 2014-2024. The study found that sensory marketing can enhance brand differentiation and consumer engagement, especially when integrated across multiple sensory touchpoints. the study highlights the importance of sensory consistency in building trust and loyalty. The reviewed studies emphasize the significant influence of sensory elements such as scent, color, music, and product packaging on consumer satisfaction, purchase intention, and decision-making processes, such as virtual reality and immersive e-commerce experiences, have also been identified as key drivers of sensory marketing success. The interaction of sensory stimuli and consumer responses is critical to developing effective marketing strategies that enhance consumer experiences and foster brand loyalty in today's competitive marketplace.